A high sphericity single crystal positive electrode material and preparation method thereof

By using the combination of elements A and B in the ternary positive electrode material of lithium-ion batteries, the growth rate of single crystal particles is adjusted, the problems of material stability and cycle life are solved, high spherical and dispersible are achieved, and the cycle performance and dynamic performance of the battery are improved.

CN117038962BActive Publication Date: 2025-03-21HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311212982.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

In the process of increasing the nickel content and upper cutoff voltage of the existing lithium-ion battery ternary cathode materials, the material stability is reduced, the cycle life is short, and the synthesis of single crystal materials requires high temperature to cause agglomeration and irregular morphology, which affects performance.

Method used

By introducing the combination of elements A and B, the growth rate of single crystal particles in different directions can be adjusted to grow evenly, reduce agglomeration, and improve spherical shape and dispersion. The specific method includes during the two high-temperature sintering process, element A promotes single crystal growth, element B inhibits growth, and ensures the uniformity and sphericality of the particles.

Benefits of technology

The high spherical and dispersibility of single-crystal positive electrode material is achieved, which reduces the occurrence of agglomeration and cracks, improves the cyclic and dynamic properties of the material, and reduces impedance growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117038962B_ABST
    Figure CN117038962B_ABST
Patent Text Reader

Abstract

A high sphericity single crystal positive electrode material, whose chemical formula is Li a Ni 1‑x‑y‑z‑v Co x M y A z B v O 2‑w , M is Mn and / or Al, the ionic radius or ionic group radius of A is greater than 85pm, the ionic radius or ionic group radius of B is not greater than 70pm, and the difference between the ionic radius or ionic group radius of A and B is not less than 45pm. The preparation method is: the positive electrode material precursor, lithium salt, compound containing A and compound containing B are mixed evenly, and then two stages of high-temperature sintering are performed. After the sintering is completed, the sintered material is crushed and sieved to obtain a single crystal positive electrode material with high sphericity. The principle that A promotes the growth of single crystals and B inhibits the growth of single crystals is used to adjust the growth rate of single crystal particles in different directions, so that the growth rate in each direction tends to be uniform, avoiding disordered excessive growth of particles in certain specific directions, and reducing agglomeration, thereby ensuring that the single crystal positive electrode material has high sphericity, roundness and high dispersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery materials, and in particular relates to a high-sphericity single crystal positive electrode material and a preparation method thereof. Background Art

[0002] LiNi, a ternary cathode material for lithium-ion batteries 1-x-y Co x M y O2 (M=Mn or Al) has the advantages of high specific capacity and good rate performance. With the development of the electric vehicle industry, higher requirements are placed on the range and service life of electric vehicles. The increase in range corresponds to the increase in material capacity. To obtain higher capacity, one aspect is to increase the nickel content of the material, and on the other hand, it is necessary to increase the upper cutoff voltage of the material. Both of these will bring great destructiveness to the stability of the material, thereby greatly reducing the cycle life of the battery.

[0003] In order to solve this problem, single crystal ternary materials came into being. By greatly increasing the primary particle size of ternary materials, each secondary particle is composed of only one or a few primary particles, which greatly reduces the grain boundaries inside the material, thereby improving the stability of the material and increasing the application voltage of the ternary material. However, since the synthesis of single crystal materials often requires higher sintering temperatures, the agglomeration and compaction of the materials are very serious. Several primary particles often agglomerate to form larger agglomerates, which are difficult to completely separate. The volume changes during the cycle and charge and discharge processes will cause cracks to grow along the grain boundaries, causing particle breakage and affecting performance. In addition, single crystal materials synthesized at high temperatures tend to grow unevenly and form irregular morphologies, which leads to uneven lithium extraction and insertion in different particles and even at different locations inside the particles, resulting in uneven discharge and affecting the performance of the material. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a single crystal positive electrode material with high sphericity and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0006] A high sphericity single crystal positive electrode material, the chemical formula of the single crystal positive electrode material is Li a Ni 1-x-y-z- v Co x M y A z B v O 2-w, wherein, 0.98≤a≤1.12, 0≤x≤0.5, 0≤y≤0.5, 0<z≤0.01, 0<v≤0.01, 0.5≤1-xyzv<1, 0≤w≤0.1; the M element is selected from one or both of Mn and Al, the ionic radius or ionic group radius of the A element is greater than 85 pm, the ionic radius or ionic group radius of the B element is not greater than 70 pm, and the difference between the ionic radius or ionic group radius of the A element and the B element is not less than 45 pm.

[0007] In the present invention, the ions or ion groups of A have a larger radius and are more difficult to enter the crystal lattice, so they can stay on the surface of the primary particles for a longer time, increase the specific surface energy of the material, make the primary particles tend to grow, and promote the growth of single crystal particles; the B element can reduce the specific surface energy of the material, thereby inhibiting the growth of single crystals. Therefore, the present invention can adjust the growth rate of single crystal particles in different directions through the combination of A and B, so that the growth rate in each direction tends to be uniform, avoid disordered excessive growth of particles in certain specific directions, reduce agglomeration, and thus obtain single crystal positive electrode materials with good sphericity and high dispersibility. If only the A element is introduced, it may cause excessive growth of single crystals, resulting in coarse single crystal particles and irregular morphology; if only the B element is added, the growth of single crystals will be inhibited, resulting in difficulty in the growth of single crystal particles. At the same time, the effects of element A and element B on crystal growth should maintain a certain difference to play a better regulatory role. If the ionic radius of element A and element B is slightly different, the difference in the regulatory effects of the two on single crystal growth will be relatively small, resulting in insufficient inhibition of the too fast growth area by element B, and insufficient promotion of the too slow growth area by element A, resulting in an unclear regulatory effect, and it is still difficult to obtain a single crystal material with good sphericity. Therefore, only by the interaction of A and B and controlling the two to maintain a certain difference in the rate of single crystal growth can the single crystal positive electrode material of the present invention be guaranteed to have good sphericity and high dispersibility.

[0008] In the above-mentioned high sphericity single crystal positive electrode material, preferably, the element A is selected from one or more of Ba, Bi, Ca, Ce, Cs, K, La, Rb, Sr, Y, F, Cl, and B;

[0009] The B element is selected from one or more of Al, Be, Mg, Mo, Nb, Ta, Ti, V, W, and Sb.

[0010] In the above-mentioned high-sphericity single-crystal positive electrode material, preferably, element A is one or more of Ba, F, Cs, La, and Sr, and element B is one or more of Nb, Mo, Sb, Ta, V, and Ti.

[0011] The high sphericity single crystal positive electrode material mentioned above preferably has a sphericity of not less than 0.85.

[0012] The high sphericity single crystal positive electrode material mentioned above, preferably, has a sphericity of not less than 0.90.

[0013] The above-mentioned high sphericity single crystal positive electrode material is preferably obtained by performing SEM test on the positive electrode material, and the area of ​​each single crystal particle therein is counted to obtain the equivalent circle diameter d1; the Feret diameter of at least 100 particles is counted to obtain d2; the sphericity of each particle is calculated to obtain σ n = , the sphericity values ​​of multiple particles are counted and the average value is taken to obtain the sphericity σ of the single crystal positive electrode material, sphericity σ = .

[0014] As a general inventive concept, the present invention also provides a method for preparing the above-mentioned high-sphericity single-crystalline positive electrode material, comprising uniformly mixing a positive electrode material precursor, a lithium salt, a compound containing A and a compound containing B, and then subjecting the resulting mixture to two-stage high-temperature sintering. After the sintering, the sintered material is crushed and sieved to obtain the high-sphericity single-crystalline positive electrode material.

[0015] In the above preparation method, preferably, the temperature of the first high-temperature sintering is 650-1000°C, and the sintering holding time is 8-12 h; the temperature of the second high-temperature sintering is 670-1050°C, and the holding time is 1-4 h.

[0016] In the above preparation method, preferably, the temperature of the second high-temperature sintering stage is 20-50° C. higher than the temperature of the first high-temperature sintering stage.

[0017] In the present invention, during the first high-temperature sintering process, the A element has a larger ion radius or ion group radius, and it is more difficult to enter the crystal lattice, so it can stay on the surface of the primary particles for a longer time, increase the specific surface energy of the material, and make the primary particles tend to grow, so as to promote the growth of single crystal particles; at the same time, the A element stays on the surface of the primary particles, melts at high temperature, and can also play the role of molten salt, penetrate into the slower growing area, and promote the crystal growth in the slower area. During the first sintering process, the B element can reduce the specific surface energy of the material, thereby inhibiting the growth of single crystals. When the material is in the high-temperature sintering process, when overgrowth occurs in certain positions or directions, the B element will preferentially be doped into the crystal lattice from these positions, thereby preferentially inhibiting the growth of single crystals in the overgrown parts, and preventing the material from growing too fast in certain directions. Through the first stage of high-temperature sintering, under the combined effect of elements A and B, the single crystal tends to grow uniformly; then through the second stage of sintering at a higher temperature, most or all of the A elements with larger ionic radius or ionic group radius can enter the crystal lattice. After the A element enters the crystal lattice, due to its larger ionic radius or ionic group radius, it will also expand the lattice spacing of the c-axis of the layered structure, which is beneficial to the embedding of lithium and promotes the formation of the layered structure.

[0018] In the above preparation method, preferably, the two high-temperature sintering stages are both carried out in an atmosphere of air or oxygen.

[0019] Compared with the prior art, the advantages of the present invention are:

[0020] (1) The present invention uses a combination of elements A and B, and utilizes the principle that element A promotes single crystal growth and element B inhibits single crystal growth, to adjust the growth rate of single crystal particles in different directions, so that the growth rate in each direction tends to be uniform, thereby avoiding disordered excessive growth of particles in certain specific directions and reducing agglomeration, thereby ensuring that the single crystal positive electrode material has high sphericity, roundness, and high dispersibility.

[0021] (2) The single crystal positive electrode material of the present invention has high sphericity and good dispersibility, which reduces the generation of single crystal agglomerates. The reduction of agglomerates means that the grain boundaries between particles are reduced, which can inhibit the growth of cracks along the grain boundaries, reduce material breakage and pulverization, and is conducive to further improving the cycle performance of the material and reducing the impedance growth during the cycle process.

[0022] (3) The single crystal positive electrode material of the present invention has high sphericity, good particle uniformity, and high particle charge and discharge uniformity, which can reduce the uneven delithiation phenomenon at different locations inside the material, reduce concentration polarization, and improve the kinetic properties of the material, which is beneficial to the capacity and rate performance of the material; at the same time, it also reduces the problem of uneven volume changes at different locations inside the material due to different degrees of delithiation, further reduces the generation of cracks and particle fragmentation, and is beneficial to improving the cycle performance of the material and reducing impedance growth.

[0023] (4) In the preparation method of the present invention, two stages of high-temperature sintering are arranged. In the first stage of high-temperature sintering, under the combined effect of A and B, the single crystal tends to grow uniformly; in the second stage of high-temperature sintering, the temperature is appropriately increased so that most or all of the A element with a larger ionic radius enters the crystal lattice. After the A element enters the crystal lattice, due to its larger ionic radius, it will also expand the lattice spacing of the c-axis of the layered structure, thereby facilitating the embedding of lithium, promoting the formation of the layered structure, and facilitating the performance of the material capacity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD diffraction pattern of the positive electrode material prepared in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1 of the present invention.

[0026] Figure 3 This is a SEM image of the positive electrode material prepared in Example 2 of the present invention.

[0027] Figure 4It is a SEM picture of the positive electrode material prepared in Comparative Example 1 of the present invention.

[0028] Figure 5 It is a SEM picture of the positive electrode material prepared in Comparative Example 2 of the present invention.

[0029] Figure 6 This is a SEM image of the positive electrode material prepared in Comparative Example 3 of the present invention.

[0030] Figure 7 It is a comparison chart of the cycle retention rates of button-type batteries assembled with the positive electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.

[0031] Figure 8 It is a SEM picture of the positive electrode material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0033] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0034] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0035] The sphericity in the following embodiments is calculated by the following method: by performing SEM test on the positive electrode material, the area of ​​each single crystal particle therein is counted to obtain the equivalent circle diameter d1; the Feret diameter of at least 100 particles is counted to obtain d2; the sphericity of each particle is calculated to obtain σ n = , the sphericity values ​​of multiple particles are counted and the average value is taken to obtain the sphericity σ of the single crystal positive electrode material, sphericity σ = .

[0036] Embodiment 1:

[0037] A high sphericity single crystal positive electrode material Li 1.01 Ni 0.698 Co 0.1 Mn 0.2 Ba 0.001 Nb 0.001 O2, sphericity σ is statistically 0.92, Ba 2+ The radius is 135 pm, Nb5+ The radius is 70 pm.

[0038] The preparation method of the high sphericity single crystal positive electrode material of this embodiment comprises the following steps:

[0039] (1) According to the ratio of nickel-cobalt-manganese precursor to lithium metal of 1:1.05, weigh the nickel-cobalt-manganese precursor Ni with D50=3.6 μm. 0.7 Co 0.1 Mn 0.2 (OH)2100 g and lithium hydroxide monohydrate 47.5 g, and weighed 0.21 g of additive A: BaCO3 and 0.29 g of additive B: Nb2O5.

[0040] (2) Add all the materials weighed in step (1) into a small mixer and mix at high speed for 5 min to ensure that the materials are fully mixed.

[0041] (3) The mixed material obtained in step (2) is placed in a box furnace for sintering. The furnace temperature is first raised from room temperature to 870°C for the first stage of high-temperature sintering. The first stage of high-temperature sintering is kept warm for 10 hours, and then the temperature is raised to 895°C for the second stage of high-temperature sintering. The second stage of high-temperature sintering is kept warm for 2 hours. The heating rate during the entire heating process is about 3°C / min. After high-temperature sintering, the mixture is naturally cooled to room temperature.

[0042] (4) The sintered material obtained in step (3) is crushed and passed through a 300-mesh sieve to obtain a single crystal positive electrode material with high sphericity, and its XRD diffraction pattern is as follows: Figure 1 As shown in the electron microscope image Figure 2 shown.

[0043] from Figure 1 It can be seen from the XRD diffraction pattern that the half-peak width of the diffraction peak of the single crystal positive electrode material synthesized in this embodiment is narrow and sharp, indicating that the crystallinity is good and conforms to the α-NaFeO2 structure. The (006) / (102) and (108) / (110) splits are good, indicating that the layered structure is intact.

[0044] from Figure 2 It can be seen from the electron microscope image that the single crystal positive electrode material particles are relatively round and well dispersed. The sphericity statistics show that the sphericity is 0.92, which is relatively high. This is due to the fact that elements A and B synergistically adjust the growth rate of particles in different directions, allowing uniform growth in all directions, thus obtaining a single crystal material with high sphericity and good dispersion.

[0045] Embodiment 2:

[0046] A single crystal positive electrode material Li with high sphericity of the present invention 1.02 Ni 0.878 Co 0.1 Mn0.2 Mo 0.002 F 0.005 O2, the sphericity σ is statistically 0.93, among which, F - The radius is 136 pm, Mo 6+ The radius is 62 pm.

[0047] The preparation method of the single crystal positive electrode material with high sphericity in this embodiment comprises the following steps:

[0048] (1) According to the ratio of nickel-cobalt-manganese precursor to lithium metal of 1:1.06, weigh the nickel-cobalt-manganese precursor Ni with D50=3.5μm. 0.88 Co 0.08 Mn 0.04 (OH)2100 g and lithium hydroxide monohydrate 47.7 g, and weighed 0.14 g of additive A: LiF and 0.31 g of additive B: MoO3.

[0049] (2) Add all the materials weighed in step (1) into a small mixer and mix at high speed for 5 minutes to ensure that the materials are fully mixed.

[0050] (3) The mixed material obtained in step (2) is placed in a box furnace for sintering. The furnace temperature is first raised from room temperature to 810°C for the first stage of high-temperature sintering. The first stage of high-temperature sintering is kept warm for 12 h, and then the temperature is raised to 840°C for the second stage of high-temperature sintering. The second stage of high-temperature sintering is kept warm for 4 h. The heating rate during the entire heating process is about 3°C / min. After high-temperature sintering, the mixture is naturally cooled to room temperature.

[0051] (4) The sintered material obtained in step (3) is crushed and passed through a 300-mesh sieve to obtain a single crystal positive electrode material with high sphericity, the electron microscope image of which is as follows: Figure 7 shown.

[0052] from Figure 3 It can be seen that the single crystal positive electrode material particles prepared in this embodiment are relatively round and have good dispersibility. The sphericity statistics are performed and the sphericity is 0.93.

[0053] Embodiment 3:

[0054] A single crystal positive electrode material Li with high sphericity of the present invention 1.00 Ni 0.495 Co 0.2 Mn 0.3 Cs 0.001 Mg 0.003 V 0.001 O2, sphericity σ is statistically 0.94, Cs + The radius is 169 pm, Mg 2+ The radius is 65 pm, V 5+ The ionic radius is 59 pm.

[0055] The preparation method of the single crystal positive electrode material with high sphericity in this embodiment comprises the following steps:

[0056] (1) According to the ratio of nickel-cobalt-manganese precursor to lithium metal of 1:1.04, weigh the nickel-cobalt-manganese precursor Ni with D50=4.0μm. 0.5 Co 0.2 Mn 0.3 (OH)2100 g and lithium carbonate 42.4 g, and weighed additive A: 0.15 g Cs2O, weighed additive B: 0.13 g MgO and 0.10 g V2O5.

[0057] (2) Add all the materials weighed in step (1) into a small mixer and mix at high speed for 5 minutes to ensure that the materials are fully mixed.

[0058] (3) The mixed material of step (2) is placed in a box furnace for sintering. The furnace temperature is first raised from room temperature to 950°C for the first stage of high-temperature sintering. The first stage of high-temperature sintering is kept warm for 8 h. The temperature is then raised to 980°C for the second stage of high-temperature sintering. The second stage of high-temperature sintering is kept warm for 4 h. The heating rate during the entire heating process is about 3°C / min. After high-temperature sintering, the mixture is naturally cooled to room temperature.

[0059] (4) The sintered material obtained in step (3) is crushed and passed through a 300-mesh sieve to obtain a single crystal positive electrode material with high sphericity.

[0060] Embodiment 4:

[0061] A single crystal positive electrode material Li with high sphericity of the present invention 0.99 Ni 0.0.947 Co 0.02 Mn 0.03 Ti 0.002 Sr 0.001 Cl 0.01 O2, the sphericity σ is statistically 0.90, among which Sr 2+ The radius is 113 pm, Cl - The radius is 181 pm, Ti 4+ The radius is 68 pm.

[0062] The preparation method of the single crystal positive electrode material with high sphericity in this embodiment comprises the following steps:

[0063] (1) According to the ratio of nickel-cobalt-manganese precursor to lithium metal of 1:1.04, weigh the nickel-cobalt-manganese precursor Ni with D50=3.5μm. 0.95 Co 0.02 Mn 0.03(OH)2100 g and lithium hydroxide monohydrate 46.8 g; and weighed additive A: 0.32 g SrCO3 and 0.23 g LiCl, weighed additive B: 0.17 g TiO2.

[0064] (2) Add all the materials weighed in step (1) into a small mixer and mix at high speed for 5 minutes to ensure that the materials are fully mixed.

[0065] (3) The mixed material of step (2) is placed in a box furnace for high-temperature sintering. The furnace temperature is first raised from room temperature to 790°C for the first stage of high-temperature sintering. The first stage of high-temperature sintering is kept at a temperature of 9 h. The temperature is then raised to 840°C for the second stage of high-temperature sintering. The second stage of high-temperature sintering is kept at a temperature of 1 h. The heating rate during the entire heating process is about 3°C / min. After high-temperature sintering, the mixture is naturally cooled to room temperature.

[0066] (4) The sintered material obtained in step (3) is crushed and passed through a 300-mesh sieve to obtain a single crystal positive electrode material with high sphericity.

[0067] Comparative Example 1:

[0068] The positive electrode material of this comparative example is Li 1.01 Ni 0.7 Co 0.1 Mn 0.2 O2, its sphericity σ is 0.78.

[0069] The difference between the preparation method of this comparative example and that of Example 1 is that BaCO3 and Nb2O5 are not added, and the other processes and conditions are exactly the same as those of Example 1.

[0070] The electron microscope image of the positive electrode material prepared in this comparative example is as follows Figure 4 As shown, from Figure 4 It can be seen that the positive electrode material particles in this comparative example have irregular morphology and many edges and corners, indicating that the growth rates in various directions are quite different, and there are many agglomerations between the particles, resulting in poor dispersion. The sphericity statistics show that the sphericity is 0.78, which is significantly lower than that in Example 1.

[0071] The positive electrode materials prepared in Example 1 and Comparative Example 1 were assembled into button cells and electrochemical performance tests were performed. The performance comparisons are shown in Tables 1 and Figure 7As shown. It can be seen that the single crystal positive electrode material in Example 1 has a very high cycle stability, which is due to its high sphericity and dispersibility. The high sphericity ensures that the degree of delithiation at different positions of the material is close, reducing the polarization caused by different degrees of delithiation at different positions, while reducing the different degrees of volume changes caused by different degrees of delithiation, thereby reducing lattice distortion. The higher sphericity and dispersibility further reduce the grain boundaries between primary particles, reduce the possibility of cracks growing along the grain boundaries, thereby reducing the generation and growth of cracks, and further reducing the growth of impedance. Therefore, the positive electrode material in Example 1 has good cycle stability and a lower impedance growth rate, while Comparative Example 1 shows relatively poor cycle stability and a higher impedance growth rate.

[0072] Comparative Example 2:

[0073] The positive electrode material of this comparative example is Li 1.01 Ni 0.7 Co 0.1 Mn 0.2 O2, its sphericity σ is 0.80.

[0074] The difference between the preparation method of this comparative example and that of Example 1 is that the additives added in this comparative example are CeO2 and Nb2O5, wherein Ce 4+ The ionic radius of Nb is 87 pm. 5+ The radius is 70 pm, and the difference in ion radius between the two is only 17 pm. Other processes and conditions are exactly the same as those in Example 1.

[0075] The electron microscope image of the positive electrode material prepared in this comparative example is as follows Figure 5 As shown, although this comparative example selects two elements with different ionic radii, the difference between the ionic radii of the two is small, and the difference in the degree of regulation of the growth rate in different directions is not large enough, and it is difficult to effectively regulate the direction of excessive growth. Therefore, the particle morphology of the material still has a certain degree of agglomeration and general dispersion. The sphericity statistics are carried out, and the sphericity is 0.80, which is lower than that of Example 1. From Table 1 and Figure 7 It can be seen that although the capacity retention rate and rate performance of comparative example 2 are higher than those of comparative example 1, and the impedance growth rate is lower than that of comparative example 1, there is still a significant gap compared with embodiment 1.

[0076] Comparative Example 3:

[0077] The sphericity σ of the positive electrode material of this comparative example is 0.83.

[0078] The difference between the preparation method of this comparative example and that of Example 1 is that, when sintering is performed after mixing, the temperature is first raised to 895°C for the first stage of high-temperature sintering, the first stage of high-temperature sintering is kept warm for 2 hours, and then the temperature is adjusted to 870°C for the second stage of high-temperature sintering, the second stage of high-temperature sintering is kept warm for 10 hours. Other processes and conditions are exactly the same as those of Example 1.

[0079] The electron microscope image of the positive electrode material prepared in this comparative example is as follows Figure 6 As shown. Although the comparative example selects the combination of Ba and Nb elements, the higher temperature is set as the first stage sintering temperature and the lower temperature is set as the second stage sintering temperature. During the first stage of high temperature sintering, Ba and Nb ions will quickly enter the lattice for doping, and the time they stay on the surface is shortened, making it difficult to effectively adjust the specific surface energy of the particle surface, resulting in poor adjustment effect on the particle sphericity. The sphericity statistics are 0.83, which is lower than that of Example 1. From Table 1 and Figure 7 It can be seen from the results that although Ba and Nb elements are added, due to the above-mentioned reasons, the sphericity of the material fails to reach the level of Example 1, so the cycle performance fails to reach the level of Example 1, and the rate performance and impedance growth performance are relatively worse.

[0080] Comparative Example 4:

[0081] Li 1.02 Ni 0.88 Co 0.1 Mn 0.2 F 0.005 O2, the sphericity σ is statistically 0.81.

[0082] The difference between the preparation method of this comparative example and that of Example 2 is that only additive A: LiF is added as an additive, and additive B: MoO3 is not added. Other processes and parameters are exactly the same as those of Example 2.

[0083] The electron microscope image of the single crystal positive electrode material of this comparative example is as follows Figure 8 As shown, from Figure 8 It can be seen that only element A is added in this comparative example. Under the effect of element A, although the particles grow relatively large, they have poor roundness, irregular shape and distinct edges and corners. According to statistics, the sphericity is 0.81.

[0084] Performance Test:

[0085] The positive electrode materials in the above embodiment and comparative example were respectively formed into CR2032 button batteries, and their electrochemical performance was tested. The experimental method is as follows:

[0086] Positive electrode sheet: The positive electrode material, conductive carbon black (SP), polyvinylidene fluoride (PVDF) are stirred and dispersed with the solvent NMP in a mass ratio of 92.5:5:2.5, coated on an aluminum foil substrate, and rolled to obtain a positive electrode sheet.

[0087] Negative electrode: lithium metal sheet.

[0088] Electrolyte: 1 mol / L LiPF6 solution, the solvent is a mixed solvent of EC and DMC, the ratio of the two is 1:2, and the additive is 1% VC.

[0089] The battery was assembled into a CR2032 button cell for battery testing at a test temperature of 25°C, a charge cutoff voltage of 4.4V, and a discharge cutoff voltage of 3.0V. The button cell was first charged and discharged once at 0.1C to test the initial capacity of the material; then it was charged and discharged once at 0.2C, 0.5C, 1C, and 2C, and the rate performance of the material was evaluated using the 2C / 0.2C capacity retention rate. Finally, the material was charged and discharged for 100 cycles at 1C to evaluate the cycle performance and impedance growth rate of the material.

[0090] The positive electrode materials prepared in the above-mentioned embodiment and comparative example were assembled into button-type batteries in the same way, and the electrochemical performance was tested. The results are shown in Table 1.

[0091] Table 1 Sphericity and electrochemical properties of positive electrode materials in various embodiments and comparative examples

[0092]

[0093] It can be seen from the test data in Table 1 that the positive electrode materials in Examples 1-4 have good cycle stability and high capacity at high voltage, because the A element and the B element synergistically regulate the growth process of the particles, so that they all have better sphericity and dispersibility. At the same time, since the materials in Examples 1-4 have better sphericity, better particle uniformity, reduced grain boundaries between class agglomerates and particles, and reduced internal charge and discharge inhomogeneity, the cracks and fragmentation generated by the material during the cycle are reduced, thereby reducing the impedance growth of the material during the cycle. In addition, the A element expands the interlayer spacing, and combined with the auxiliary effect of the B element, it can avoid excessive and irregular growth of the material, thereby ensuring that the positive electrode material of the present invention has better rate performance.

Claims

1. A high sphericity single crystal positive electrode material, characterized in that: The chemical formula of the single crystal positive electrode material is Li a Ni 1-x-y-z-v Co x M y A z B v O 2-w , wherein, 0.98≤a≤1.12, 0≤x≤0.5, 0≤y≤0.5, 0<z≤0.01, 0<v≤0.01, 0.5≤1-xyzv<1, 0≤w≤0.1; the M element is selected from one or both of Mn and Al, the ionic radius or ionic group radius of the A element is greater than 85 pm, the ionic radius or ionic group radius of the B element is not greater than 70 pm, and the difference between the ionic radius or ionic group radius of the A element and the B element is not less than 45 pm; the sphericity of the single crystal positive electrode material is not less than 0.85; Element A is selected from one or more of Ba, Bi, Ca, Ce, Cs, K, La, Rb, Y, F, Cl, and B; The B element is selected from one or more of Al, Be, Mg, Mo, Nb, Ta, V, W, and Sb; the area of ​​each single crystal particle is counted by SEM test on the positive electrode material to obtain the equivalent circle diameter d1; the Feret diameter of at least 100 particles is counted to obtain d2; the sphericity of each particle is calculated to obtain σ n = , the sphericity values ​​of multiple particles are counted and the average value is taken to obtain the sphericity σ of the single crystal positive electrode material, sphericity σ = The single crystal positive electrode material is prepared by the following preparation method: the positive electrode material precursor, lithium salt, compound A and compound B are evenly mixed, and then the obtained mixture is subjected to two-stage high-temperature sintering. After the sintering, the sintered material is crushed and sieved to obtain the high-sphericity single crystal positive electrode material, wherein the temperature of the first stage of high-temperature sintering is 650-1000°C, and the sintering insulation time is 8~12 h; the temperature of the second stage of high-temperature sintering is 670~1050°C, and the insulation time is 1~4 h. The temperature of the second stage of high-temperature sintering is 20~50°C higher than that of the first stage of high-temperature sintering.

2. The high sphericity single crystal positive electrode material according to claim 1, characterized in that: The sphericity of the single crystal positive electrode material is not less than 0.

90.

3. A method for preparing a high sphericity single crystal positive electrode material, characterized in that: The chemical formula of the single crystal positive electrode material is Li a Ni 1-x-y-z-v Co x M y A z B v O 2-w , wherein 0.98≤a≤1.12, 0≤x≤0.5, 0≤y≤0.5, 0<z≤0.01, 0<v≤0.01, 0.5≤1-xyzv<1, 0≤w≤0.1; the M element is selected from one or both of Mn and Al, the ionic radius or ionic group radius of the A element is greater than 85 pm, the ionic radius or ionic group radius of the B element is not greater than 70 pm, and the difference between the ionic radius or ionic group radius of the A element and the B element is not less than 45 pm; the sphericity of the single crystal positive electrode material is not less than 0.85; the A element is selected from one or more of Ba, Bi, Ca, Ce, Cs, K, La, Rb, Y, F, Cl, and B; the B element is selected from one or more of Al, Be, Mg, Mo, Nb, Ta, V, W, and Sb; the positive electrode material is subjected to SEM testing, and the area of ​​each single crystal particle therein is counted to obtain an equivalent circle diameter d1; the Feret diameter of at least 100 particles is counted to obtain d2; the sphericity of each particle is calculated to obtain σ n = , the sphericity values ​​of multiple particles are counted and the average value is taken to obtain the sphericity σ of the single crystal positive electrode material, sphericity σ = The preparation method comprises uniformly mixing a cathode material precursor, a lithium salt, a compound containing A and a compound containing B, and then subjecting the obtained mixture to two-stage high-temperature sintering. After the sintering, the sintered material is crushed and sieved to obtain the high-sphericity single crystal cathode material, wherein the temperature of the first stage of high-temperature sintering is 650-1000°C, and the sintering holding time is 8-12 h; the temperature of the second stage of high-temperature sintering is 670-1050°C, and the holding time is 1-4 h. The temperature of the second stage of high-temperature sintering is 20-50°C higher than that of the first stage of high-temperature sintering.

4. The preparation method according to claim 3, characterized in that: Both high-temperature sintering stages are carried out in an atmosphere of air or oxygen.

Citation Information

Patent Citations

  • Method for one-step low-temperature preparation of large-particle-size single-crystal ternary positive electrode material

    CN114665090A